Spatial variation in stable isotopic composition of organic matter of macrophytes and sediments from a small Arctic lake in west Greenland. Issue 1 (1st January 2018) - Thompson, Hilary A.; White, Jeffrey R.; Pratt, Lisa M.
ABSTRACT: Stable isotope compositions of organic carbon (δ 13 Corg ) and nitrogen (δ 15 N) in macrophytes and sediments are useful in assessing sources of lake productivity and diagenesis of organic matter from formation through sedimentation to decomposition. Despite the increasing importance of high-latitude landscapes to carbon cycling under amplified and accelerating warming in the Arctic, the high density of small closed-basin lakes in this landscape, and the utility of stable isotopes in the study of carbon dynamics, limited data are available on within-lake spatial variability of δ 13 Corg and δ 15 N in these systems. The goal of this study was to investigate the spatial variability in stable isotopic composition of three dominant macrophyte species ( Hippuris vulgaris, Eriophorum angustifolium, Warnstorfia exannulata ) and sediments from littoral and profundal areas of a single closed-basin system among the common small Arctic lakes that populate the ice-free margin of Greenland. The range in δ 13 Corg of macrophytes (−33.9‰ to −27.1‰) was within the typical range of plants utilizing the C3 pathway for carbon fixation. No notable differences were observed in δ 13 Corg between segments of the individual macrophytes (emergent, submergent, and root tissues), indicating that the isotopic fractionation of carbon was similar throughout the plant. Between-species variations in δ 13 Corg were small, but significant ( p  < 0.01), with the moss most depleted in 13 C. The range of δ 15 N in littoral and profundal sediments (−0.52‰ to 1.33‰) was small, with littoral surface sediments 1‰ less enriched in 15 N than surface sediments in the profundal zone. The C/N ratios of macrophytes (mean ± SD: 27.0 ± 12.6), littoral sediments (mean ± SD: 11.0 ± 1.0), and profundal sediments (mean ± SD: 9.1 ± 0.9) point to diagenetic alteration. Combined isotopic and elemental (C/N) compositions of littoral and profundal sediments suggest that organic matter accumulating in the study lake originate primarily from in-lake primary production of macrophytes. Terrestrial sources are likely minor because of the hydrologically closed basin and limited aeolian inputs, suggesting that the majority of organic matter produced by the dominant littoral macrophyte community was decomposed between production and sediment deposition.